A primogenius study on characterisation of c-Si solar cell. (1st January 2013) - Bhattacharjee, Subhadeep; Biswas, Rashmi
The use of solar photovoltaic (PV) as distributed energy resources is increasingly being pursued as a supplement and alternative to conventional grid electricity. It has become an important source of energy because of its high reliability, requirement of very little maintenance and capability of generating power with no noise and emissions. Silicon solar cell as renewable energy resource has been extensively studied in the last couple of years. In view of enormous application and interest of crystalline (c-Si) silicon solar cell for PV power generation across the world, an elementary study has been tried to be carried out in this paper to comprehend the performance of the silicon solar cell. Basic and critical characterisation and analysis have been performed with PC1D modelling. Also the effect of back surface field layer on efficiency is observed with and without rear passivation.